Development of the method for standardization of the medicinal plant raw material of Cichorium intybus L. herb by the total amount of hydroxycinnamic acid derivatives - Kseniya Proskurina; Olga Yevtifieieva; Olga Mala; Viktoriya Mashtaler (Pensoft Publishers, 2021)
The purpose of the research is to work out a routine method for the quantitative determination of the total amount of hydroxycinnamic acids in chicory herb growing in Ukraine. The presence of chlorogenic and caffeic acids was experimentally proven by comparing the TLC profiles of solutions of the chicory extract and standard substances of hydroxycinnamic acids. According to the chromatogram, the chemical composition of the ethanol extracts was qualitatively constant and did not depend on the series of plants collected in different places (7 regions of Ukraine) and in different years (2017 and 2018). The water-alcohol solutions of 8 chicory herb samples had the absorption maximum at the wavelength range from 326 to 330 nm, which was typical for phenolic acids. Chlorogenic acid was chosen as a marker substance for the quantitative determination by direct spectrophotometry. The value of the specific absorbance (556.21(λ=327 nm)) of chlorogenic acid in the concentration of 10.08 µg/ml in ethanol 50% was determined. The total amount of hydroxycinnamic acids was found to be 1.87% for the sample of 2017, for the samples of 2018 in the range of 4.00-6.61%. The method proposed is acceptable for standardization of the medicinal plant raw material.